FUNDAMENTALISME ISLAM: Kajian Fenomena Sosio-Religius - Mubarak, Zulfi (ULUL ALBAB Jurnal Studi Islam, 2002)
Fundamentalism is inescabaly rooted in a specific Protestant experince whose principle theological premise is that the Bible is the true word of God and should be understood literally. ln this regard, it makes no sense to speak of fundamentalist Islam because one of the core element of the creed of all believing Muslim is that the Qur 'an is the literal (absolutely true) word of God as revealed ti his Prophet Muhannad through the intermediacy of the angel Gabriel.